Employee Perception of Fairness in the Performance Appraisal Process and Its Impact on Performance in Indonesian Startups - Nanda Hidayati; Muhammad Syafri; Syamsulbahri Syamsulbahri; Muhamad Akbar; Slamet Sutrisno (The Eastasouth Management and Business, 2025)
This study investigates the relationship between employee perceptions of fairness in the performance appraisal process and employee performance in Indonesian start-up companies. A quantitative approach was employed, with data collected from 115 employees using a Likert scale-based survey. The data were analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS 3). The results reveal that all three dimensions of fairness—procedural fairness, distributive fairness, and interactional fairness—significantly influence employee performance. Procedural fairness had the strongest positive relationship with performance, followed by interactional fairness and distributive fairness. The findings suggest that employees who perceive the appraisal process as fair in terms of consistency, outcomes, and interpersonal treatment are more likely to exhibit higher job performance. The study highlights the importance of fairness in performance appraisals for fostering a productive work environment in start-up companies.